Artistic Realization and Modernity: Guillevic and Cézanne - Prevots, Aaron (Dalhousie French Studies, 2024)
Through Paul Cézanne (1839-1906) and Eugène Guillevic (1907-1997), this article probes artistic realization as a topos in modern art since the 1800s. Interart discourse including art historical contexts and Guillevic’s early notebook entries in Écrits intimes (2019) help us assess a foremost influence and implicit mentor who taught the poet to favor a concrete, personal, textured, highly focused vision of things seen. At issue in the analyses is the artist’s or poet’s diligent crafting of a perspective that valorizes earthy materiality filtered through the observer’s subjective sensations, which often draw inspiration from immediate surroundings in favorite natural locales. Inclus, in particular, which addresses the poem as sacred space, proposes like Cézanne’s artworks with their colorful constructive brushstrokes that authenticity need not mean direct transcription of the real. Close readings accompany Guillevic as he dialogues indirectly with Cézanne, affirming his own ability to see clearly and make his oeuvre a ritualized fête while exemplifying controlled contemporary lyricism and thus important aspects of French literary modernity.